Krishnamurti on Education
This book is the outcome of talks and discussions held by J. Krishnamurtiwith the students and teachers of Rishi Valley School in Andhra Pradesh andRajghat Besant School in Varanasi. Krishnamurti regards education as ofprime significance in the communication of that which is central to thetransformation of the human mind and the creation of a new culture. As thetopies in these stimulating talks and discussions reveal, he questions thevery roots of our culture so that a comprehensive view on educationemerges.Krishnamurti\\\\\\\'s challenge is addressed not only to the structure ofeducation but to the very nature and quality of man\\\\\\\'s mind and life. Unlikeall other attempts to salvage or suggest alternatives to the educationalsystem, his approach breaks through the frontiers of particulars culturesand establishes an entirely new set of values. To Krishnamurti a new mindis possible only when the religious spirit and the scientific attitude formpart of the same consciousness. While he gives emphasis to the cultivationof the intellect, he lays far greater stress on a heightened criticalawareness of the inner and outer world.